Double loop hysteresis in direct current dependent dielectric permittivity of SrTiO 3 - Gevorgian S.; Eriksson A.; Deleniv A.; Pandey D. (My University, 2025)
Experimental double loop hysteresis in dc field dependent dielectric permittivity in bulk single crystal SrTiO 3 is reported. Small signal measurements of the permittivity are performed in the frequency range 0.5-1.5 GHz at temperatures below 77 K using electrically thin circular parallel-plate resonators. The dielectric permittivity is extracted form the measured resonant frequency. The double loop hysteresis may be caused by field induced local paraelectric/ferroelectric phase transitions, and/or switching (polarization reversal) in local opposing ferroelectric domains associated with symmetry breaking impurities/structural defects. © 2002 American Institute of Physics. © 2002 American Institute of Physics.